IMPLEMENTASI PROGRAM “JO KAWIN BOCAH” SEBAGAI UPAYA PENCEGAHAN PERNIKAHAN USIA ANAK DI PROVINSI JAWA TENGAH - Yuniar, Mutiara Nuraini; Astuti, puji -; -, Supratiwi - (Journal of Politic and Government Studies, 2025)
Child marriage is a social problem that must be the focus of the Central Java Provincial Government. One of the efforts made in Central Java Province is to create and implement the “Jo Kawin Bocah” Program to reduce the number of child marriages. The purpose of this study is to determine how the implementation along with the supporting and inhibiting factors of the “Jo Kawin Bocah” Program in Central Java Province. The theory used is the theory of public policy implementation by Van Meter and Van Horn. This study uses a qualitative research method. Information and data were obtained using in-depth interview techniques and literature studies. The results of the study indicate that the implementation of the “Jo Kawin Bocah” Program in Central Java has been quite successful, as evidenced by the decrease in the number of child marriages. Supporting factors for implementing “Jo Kawin Bocah” are strong regulations, a common perspective to reduce the number of child marriages, the potential for the community to be involved in Jo Kawin Bocah, and services provided by Puspaga and the Central Java Children's Forum. Meanwhile, factors inhibiting implementation are cultural factors, technological developments, and free association